Protection of minority rights: System of guarantees in the Covenant of the League of Nations - N.G. Nougaeva; Ju.S. Ovchinnikova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The relevance of this paper stems from the fact that today, as we are approaching the 100 year anniversary of the creation of the League of Nations, a new vision is increasingly required in assessment of its legacy through the prism of modern international law. Further study in this field is necessary considering that the history of the League of Nations still remains a source of legal and political experience for the modern United Nations. The paper analyzes the stages of creation of a system for guarantees protecting the rights of national minorities within the framework of the League of Nations. Although this system was clearly very politicized in its nature, its novelty and integration of new elements of better quality for protection of minority rights cannot be denied. The primary goal of the paper is to reveal the reasons for the ultimate weakening of the League of Nations procedure for addressing petitions concerning violations of minority rights. In order to achieve this goal, the author uses the methods of objective, historical, and scientific analysis. As a result of the analysis, the conclusion has been made that the basic characteristics of the process for addressing violations of minority rights were established in the first three years after the League of Nations had been organized. Furthermore, the key trends undermining this process became apparent in less than a year following the establishment of the League of Nations. The paper sums up that the flaws of the process included the lack of experience and understanding among the members of the “committees of the three” in the field of minority rights, as well as the limited time allotted for the council's deliberation sessions. These factors lead to the deliberation on individual petitions dragging for years and also contributed to the gradual rise to greater prominence of the minority section established within the secretariat of the League of Nations. The results of this study can serve as a foundation for further scientific analysis of issues related to the protection of minority rights and human rights in general.